Which skills protect graduates against a slack labour market?. (March 2017) - HUMBURG, Martin; de GRIP, Andries; van der VELDEN, Rolf
Abstract: This article explores the relationship between graduates' skills and their risk of over‐education and unemployment in 17 European countries. Distinguishing between field‐specific and academic skills, the authors find that, as predicted by the crowding‐out hypothesis, field‐specific skills offer more protection against the risk of over‐education when the excess labour supply in the occupational domain of the graduate's field of study increases. Conversely, academic skills have that effect when excess supply in the overall labour market is higher. Field‐specific skills also protect graduates against the risk of unemployment, whereas graduates' level of academic skills appears to be unrelated to the risk of becoming unemployed.